2007
DOI: 10.1681/asn.2006101167
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein C in Renal Dysfunction after Polymicrobial Sepsis

Abstract: Protein C (PC) plays an important role in vascular function, and acquired deficiency during sepsis is associated with increased mortality in both animal models and in clinical studies. This study explored the consequences of PC suppression on the kidney in a cecal ligation and puncture model of polymicrobial sepsis. This study shows that a rapid drop in PC after sepsis is strongly associated with an increase in blood urea nitrogen, renal pathology, and expression of known markers of renal injury, including neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 55 publications
(52 reference statements)
5
49
0
1
Order By: Relevance
“…We observed a nuclear pattern of positive signals in tubular cells as had already been described by others. [24][25][26] The expression was increased in Gly-AKI ( Figure 3B) and significantly exacerbated by silymarin treatment ( Figure 3C). The quantitative analysis confirmed statistically significant increase in the expression of cleaved caspase-3 in Gly-AKI + silymarin ( Figure 3D).…”
Section: Effects Of Silymarin On Renal Function and Tubular Injury Inmentioning
confidence: 96%
“…We observed a nuclear pattern of positive signals in tubular cells as had already been described by others. [24][25][26] The expression was increased in Gly-AKI ( Figure 3B) and significantly exacerbated by silymarin treatment ( Figure 3C). The quantitative analysis confirmed statistically significant increase in the expression of cleaved caspase-3 in Gly-AKI + silymarin ( Figure 3D).…”
Section: Effects Of Silymarin On Renal Function and Tubular Injury Inmentioning
confidence: 96%
“…Nevertheless, the criteria used for renal dysfunction in that study (that is, oliguria) are questionable, because oliguria cannot be considered a fully accurate marker of kidney damage. Furthermore, animal studies have suggested a protective effect of APC in sepsis-induced kidney injury (216,217).…”
Section: Therapeutic Implications and Perspectivesmentioning
confidence: 99%
“…10 Moreover, low levels of PC have been highly associated with renal dysfunction and pathology in models of AKI. 11 During vascular insult, PC becomes activated by the endothelial thrombin-thrombomodulin complex, and the activated protein C (APC) exhibits both antithrombotic and cytoprotective properties. We have previously demonstrated that APC administration protects from renal dysfunction during cecal ligation and puncture and after endotoxin challenge.…”
mentioning
confidence: 99%
“…We have previously demonstrated that APC administration protects from renal dysfunction during cecal ligation and puncture and after endotoxin challenge. 11,12 In addition, recombinant human APC [drotrecogin alfa (activated)] has been shown to reduce mortality in patients with severe sepsis at high risk of death. 13 Although the ability of APC to protect from organ injury in vivo is well documented, 11,14,15 the precise mechanism mediating the response has not been ascertained.…”
mentioning
confidence: 99%